2014
DOI: 10.5762/kais.2014.15.7.4272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sun screen utilizing Porphyra-334 derived from Ocean Algae for skin protection

Abstract: One of the most effective ways of preventing skin aging is to protect the skin from UV radiation, which was identified as the primary cause of photoaging. Therefore, it is necessary to develop natural and environment-friendly materials to the human skin. This study examined the effects of MAAs extracted from Chlamydononas hedleyi on UV protection and anti-inflammation in human skin cells. The function of porphyra-334 in the skin, which was isolated and purified from MMAs mixture, was tested in terms of its UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Seaweeds-derived MAAs have also been tested for their anti-inflammatory properties in UV-irradiated HaCaT cells [ 137 ]. Porphyra-334 treatments suppressed COX-2 expression and one of the main cytotoxic mediators participating in the innate response in mammals [ 138 ].…”
Section: Seaweed Compounds As Potential Sources Of Anti-photoagingmentioning
confidence: 99%
“…Seaweeds-derived MAAs have also been tested for their anti-inflammatory properties in UV-irradiated HaCaT cells [ 137 ]. Porphyra-334 treatments suppressed COX-2 expression and one of the main cytotoxic mediators participating in the innate response in mammals [ 138 ].…”
Section: Seaweed Compounds As Potential Sources Of Anti-photoagingmentioning
confidence: 99%
“…MAAs have been reported to have antioxidant effects and protective effects against ultraviolet rays and photooxidative stress (Shick et al, 2002;Venkatraman et al, 2019;Ying et al, 2019). Particularly, shinorine and prophyra-334 isolated from microalgae not only protects against cytotoxicity caused by UV irradiation but also suppresses the expression of COX-2, an inflammationrelated gene (Cho et al, 2014;Jung et al, 2014). A recent study reported that laver contains MAAs, including shinorine and porphyra-334 (Ying et al, 2019), and these compounds have surfaced as some of the beneficial components of laver.…”
Section: Shinorine and Porphyra-334 Contentmentioning
confidence: 99%